Spreading the Word: Oral Transmission of the Bogomil Teachings, its Symbolism, and Biblical Exegesis - Radovanović, Bojana (Studia Ceranea, 2021)
The oral biblical exegesis and oral transmission, or the unwritten tradition, represent pillars in the circulation of texts and ideas since the very dawn of Christianity, both in orthodox and heterodox circles. Namely, this vast topic encompasses the concepts related to the concepts of the written sources and the spoken word, and their interrelation, and, furthermore, to the symbolism of the ear, Logos, and secret teachings (arcana). The role and impact of the oral transmission will be examined on the example of the Bogomils, and this paper will re-assess the importance and function of the oral transmission of the Bogomil doctrine. Therefore, the Biblical exegesis will also be analyzed in that key, and the question of the Bogomil preachers will be addressed. More broadly, the oral transmission of the Bogomil teachings can be observed as one of the modi operandi that the Bogomils resorted to in the aim of propagating their ideas, as well as possibly their interpretative manner to approach the Scriptural material and parables.